2013
DOI: 10.1681/asn.2012050536
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Disorders and Dementia in CKD

Abstract: Epidemiologic data suggest that individuals at all stages of CKD have a higher risk of developing cognitive disorders and dementia. This risk is generally explained by the high prevalence of both symptomatic and subclinical ischemic cerebrovascular lesions. However, other potential mechanisms, including direct neuronal injury by uremic toxins, could also be involved, especially in the absence of obvious cerebrovascular disease. We discuss the prevalence and characteristics of cognitive disorders and dementia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
438
1
9

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 492 publications
(458 citation statements)
references
References 85 publications
10
438
1
9
Order By: Relevance
“…The biological mechanisms underlying renal disease are consistent with those evident in diabetes and hypertension, such as neuronal damage, oxidative stress, thrombosis, vascular lesions, and atherosclerosis [2,4,12,13]. Physical activity has been shown to elicit metabolic and affectual improvements on the aforementioned physiological and psychological determinants of chronic disease, as well as improving the functional and social quality of life [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…The biological mechanisms underlying renal disease are consistent with those evident in diabetes and hypertension, such as neuronal damage, oxidative stress, thrombosis, vascular lesions, and atherosclerosis [2,4,12,13]. Physical activity has been shown to elicit metabolic and affectual improvements on the aforementioned physiological and psychological determinants of chronic disease, as well as improving the functional and social quality of life [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 74%
“…Mental health decline also poses a significant risk for individuals diagnosed with milder stages of kidney disease [2]. The Cardiovascular Health Cognition Study examined the prevalence of vascular dementia over time, finding the diagnosis of moderate renal disease predicted increased metabolic biomarkers, known to contribute to poor mental health, and vascular dementia after 6 years [3].…”
Section: Introductionmentioning
confidence: 99%
“…Khatri et al [7] prospectively studying a cohort of multiethnic stroke-free patients with CKD observed that CKD correlated with cognitive decline even in patients with mildly impaired renal function. Early diagnosis and prompt treatment to retard the progress of cognitive decline in patients with CKD is very important, as poor cognitive function has been associated with a greater risk of death in dialysis patients, poor compliance to treatment, and increased occurrence of cerebrovascular disease and longer hospital stay [3,[8][9][10]. Apart from being a significant contributor to mortality, it is a key determinant of the quality of life because the patient's decision making and adherence to both pharmacological and nonpharmacological management principles depend on a sound cognitive state [11].…”
Section: Introductionmentioning
confidence: 99%
“…A positive correlation has also been established between cognitive impairment in CKD and serum creatinine, urea, uric acid, and serum calcium levels [15]. Reports have also highlighted the high incidence of cerebral ischemia in the etiopathogenesis of cognitive impairment in CKD, and this is thought to be due to the shared microvascular risk factors between CKD and brain ischemia [16]. Systematic cardiovascular risk factors directly predict poorer executive function [17].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review, Bugnicourt et al (10) proposed a detailed model of the complex pathophysiology of cognitive impairment in CKD that emphasizes three primary pathways to cognitive impairment: traditional cardiovascular risk factors, nontraditional factors such as inflammation, oxidative stress, and hypercoagulable state, and uremic toxins including cystatin C. In this model, these pathways, in turn, lead to either primarily vascular cognitive impairment or neurodegenerative cognitive impairment. However, a combination of multiple pathologies is more likely.…”
mentioning
confidence: 99%